Trilhando a estrada de tijolos amarelos da educação ambiental com os jogos educativos - Firmino, Anaisa Moreira (2010)
In recent years the ludic has been studied by several areas of knowledge and numerous authors as a facilitator way in the teaching-learning process. Its importance, contribution and benefit to the child s development and learning in affective, physical, cognitive, social and psychic aspects are evidenced in several studies worldwide. In this work we made a general approach on the issue of play, we analyzed the meaning assigned to play, we reflected and discussed about the importance and advanced for the emotional, social, affective and psychic development of the children and the reason and what for they play. We approached issues related to play with regard to education; we examine the ludic activity (educational games) as a pedagogical tool for teaching within the classroom as an aid in Environmental Education. A recent branch within the Environmental Education has tried to bring the playful (environmental playfulness) as sensitizing and facilitating ways for environmental issues primarily with work done with children. This paper presents the results achieved at the Municipal School Sobradinho, in Uberlândia (MG), with teachers and students form 6th and 7th grade of elementary school. We evaluated four educational games that work with environmental issues as a tool in the teaching-learning process in the classroom. The results indicate that the ludic means is configured as an excellent methodological tool for teaching children to work with issues related to the environment. It is a means that gives pleasure and joy to children and therefore they feel more willing to learn.